2023
DOI: 10.18502/ijph.v52i6.12959
|View full text |Cite
|
Sign up to set email alerts
|

Linc01614 Regulates the Proliferation, Apoptosis, and Chemotherapy Resistance in Esophageal Squamous Cell Carcinoma by Targeting Mir-4775

Abstract: Background: Esophageal squamous cell carcinoma (ESCC), a widely known esophageal disease, severely affects people's health. Numerous investigations demonstrated that long non-coding RNAs (lncRNAs) performed key jobs inside a wide scope of organic cycles and stand out in malignant growth. Our study planned to investigate the roles and mechanisms of linc01614 in ESCC. Methods: A Total of 60 ESCC tissue samples including 30 patients with cisplatin sensitivity and 30 patients with cisplatin resistance, who r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Accumulating evidence indicated that LINC01614 was abnormally expressed in diverse malignant tumor tissues, including osteosarcoma ( Cai et al, 2021 ), gastric cancer ( Wu et al, 2021 ), glioma ( Wang et al, 2020b ), breast cancer ( Wang et al, 2019a ), and lung cancer ( Sun and Ling, 2019 ), and was closely correlated with clinical pathology indicators and could predict prognosis ( Wang et al, 2020a ; Dong et al, 2021 ). Knockdown of LINC01614 inhibited cell growth, migration, and invasion of THCA and esophageal squamous cell carcinoma ( Wei et al, 2023 ). In BRCA, LINC01614 as a hazard prognosis factor was associated with the HR+/HER2 + molecular subtype ( Li et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence indicated that LINC01614 was abnormally expressed in diverse malignant tumor tissues, including osteosarcoma ( Cai et al, 2021 ), gastric cancer ( Wu et al, 2021 ), glioma ( Wang et al, 2020b ), breast cancer ( Wang et al, 2019a ), and lung cancer ( Sun and Ling, 2019 ), and was closely correlated with clinical pathology indicators and could predict prognosis ( Wang et al, 2020a ; Dong et al, 2021 ). Knockdown of LINC01614 inhibited cell growth, migration, and invasion of THCA and esophageal squamous cell carcinoma ( Wei et al, 2023 ). In BRCA, LINC01614 as a hazard prognosis factor was associated with the HR+/HER2 + molecular subtype ( Li et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that some lncRNAs can serve as early diagnosis biomarkers or prognosis parameters in different human carcinomas ( de Santiago et al, 2021 ). Emerging evidence suggests a compelling correlation between LINC01614 expression and prognostic outcomes of lung cancer ( Liu et al, 2022 ), gastric cancer ( Chen et al, 2021 ), and ESCA prognosis ( Wei et al, 2023 ). LINC01614 was relevant to the HR+/HER2 + breast cancer molecular subtype and accelerated breast cancer cell proliferation and migration by TGF-β and focal adhesion kinase (FAK) signaling ( Vishnubalaji et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, after cisplatin treatment, lncRNA non-coding repressor of NFAT was upregulated, contributing to cisplatin resistance by downregulating miR-31 in KYSE510 ( 116 ). Another study showed that Linc01614/miR-4775 enhanced proliferation and cisplatin resistance in EC9706 and KYSE30 cells, while inhibiting cell apoptosis and promoting CDX growth in EC9706 ( 117 ). In addition, lncRNA HCP5 inhibited UTP3 small subunit processome component ubiquitination and degradation, leading to the recruitment of c-MYC to activate vesicle associated membrane protein 3 expression and inhibited caspase-dependent apoptosis, ultimately resulting in cisplatin resistance in CDX (KYSE150) ( 118 ).…”
Section: Lncrnas Upregulated In Esccmentioning
confidence: 99%